Global Financial Stability Report, September 2002 : Market Developments and Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2002)
This September 2002 issue of the Global Financial Stability Report highlights that during the second quarter of 2002, a sharp erosion of investor confidence heightened risk aversion and growing concerns about the strength and durability of the global recovery. The pace and quality of corporate earnings had repercussions in all of the major equity, credit, and foreign exchange markets. Market adjustments occurred against the background of the bursting of the telecom, media, and technology bubble, which exposed a culture of irrational exuberance, and sometimes greed, among many buyers, sellers, and intermediaries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet